STRATEGI MEMAKSIMALKAN NILAI KEKAYAAN PEMEGANG SAHAM (SHAREHOLDERS WEALTH) MELALUI KINERJA KEUANGAN PERUSAHAAN KONSTRUKSI (Studi Empiris Pada Perusahaan Sektor Konstruksi di Bursa Efek Indonesia Periode 2014-2018) - Setiawan, Yudi; Etty M, Endang; Supriyadi, Edy (SEKOLAH PASCASARJANA PRESS, 2020)
The increase in shareholder wealth influenced by accounting measures that indicate the company's financial condition. Some financial ratios that are used as indicators of shareholder's wealth, among others: leverage, (DER), profitability (ROE) and dividend policy (Dividend Payout Ratio / DPR). In construction companies listed on the Indonesia Stock Exchange, within 5 years of observation, namely 2014-2018, showed Return to Equity, Debt to equity ratio had a positive effect on shareholder's wealth, while Dividend payout ratio had no effect. The return to equity ratio has a positive effect on the dividend payout ratio while the Debt to equity ratio has a negative effect on strategies to increase shareholder's wealth through the optimization of fundamental financial performance such as DER, ROE, with dividend payout ratios that are proportional to revenue.